FINANCIAL ACTIVITY IN THE REPUBLIC OF UZBEKISTAN - Hayitkhon Mahammadjonovna Ismoilova; Oyatillo Khairullo ugli Rakhmatullaev (Galaxy International Interdisciplinary Research Journal, 2022)
The organization and mechanisms of the financial system of the Republic of Uzbekistan are explained in the article. In addition, information about the concept of finance, its origin and its importance today is widely explained through sources.